Relationship between periodontal destruction and gene mutations in patients with familial Mediterranean fever. Issue 7 (July 2016) - Sezer, Ufuk; Şenyurt, Süleyman; Özdemir, Eda; Zengin, Orhan; Üstün, Kemal; Erciyas, Kamile; Kısacık, Bünyamin; Onat, Ahmet
Abstract Recent studies have shown that genetic factors involved in the host responses might determine the disease severity for both familial Mediterranean fever (FMF) and periodontitis. The present study aimed to investigate the relationship of FMF with periodontitis and to search for the potential association between periodontitis and MEFV gene missense variations in patients with FMF. The study consisted of 97 FMF patients and 34 healthy volunteers. FMF patients were classified according to the kind of MEFV gene mutation: (1) patients with homozygous M694V gene mutation, (2) patients with heterozygous M694V gene mutation, and (3) patients with MEFV gene different mutations. Gingival Index (GI), Plaque Index (PI), probing pocket depth (PD), and clinical attachment level (CAL) were measured in all participants. The results of multivariate logistic regression showed a highly significant association between homozygous M694V gene mutation and periodontitis in FMF patients (p  < 0.05). After adjusting for potential confounders (smoking, body weight, age, and gender), FMF patients with homozygous M694V gene mutation were 3.51 (1.08–11.45) times more likely to present periodontitis than the other FMF patients. These results indicate that the presence of homozygous M694V gene mutation seems to increase the risk for periodontitis in FMF patients.